2018
DOI: 10.1038/s41598-017-18405-8
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the properties of the cell membrane due to glycosphingolipid accumulation in a model of Gaucher disease

Abstract: Gaucher disease is a lysosomal storage disease characterized by the malfunction of glucocerebrosidase resulting in the accumulation of glucosylceramide and other sphingolipids in certain cells. Although the disease symptoms are usually attributed to the storage of undigested substrate in lysosomes, here we show that glycosphingolipids accumulating in the plasma membrane cause profound changes in the properties of the membrane. The fluidity of the sphingolipid-enriched membrane decreased accompanied by the enla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 74 publications
(95 reference statements)
0
43
0
Order By: Relevance
“…GlcCer has been implicated in altering the physical properties of membranes; for example, increased GlcCer results in decreased membrane fluidity (59, 60). In addition, a recent paper demonstrated that cells taken from patients with Gaucher disease displayed restricted lateral lipid mobility and exhibited reduced rates of transferrin receptor endocytosis (61). Coupled with our findings, these reports suggest that the disruption in endocytosis that we observe in GBA KO cells for critical cargos, including pathogenic viruses and growth factor receptors, may be due in part to an alteration in the biophysical properties of cellular membranes.…”
Section: Discussionmentioning
confidence: 99%
“…GlcCer has been implicated in altering the physical properties of membranes; for example, increased GlcCer results in decreased membrane fluidity (59, 60). In addition, a recent paper demonstrated that cells taken from patients with Gaucher disease displayed restricted lateral lipid mobility and exhibited reduced rates of transferrin receptor endocytosis (61). Coupled with our findings, these reports suggest that the disruption in endocytosis that we observe in GBA KO cells for critical cargos, including pathogenic viruses and growth factor receptors, may be due in part to an alteration in the biophysical properties of cellular membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lipid rafts, particularly those enriched in ceramide, are required for formation at least one type of EV [ 78 ]. Membrane changes such as those caused by GCase deficiency, including accumulation of glucosylceramide and altered ceramide levels [ 80 , 81 ], could alter EV functioning at any stage from formation to internalization by a recipient cell. Either increased or decreased probability of ceramide-dependent EV formation could lead to increased overall EV production, as suppression of one type of EV has been shown to cause overproduction of another type [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation hints to the possible impact of Cer:GlcCer ratio in defining the number and shape of lysosomes, with the caveat that the asymmetric membrane composition may add a further layer of complexity. Interestingly, the authors observed decreased membrane fluidity in cells treated with the GBA inhibitor conduritol B epoxide and in GD patient derived cells (Batta et al, 2018; Pavićević et al, 2018). In addition to the GlcCer:Cer ratio, it is also important to consider the membrane fraction of cholesterol present.…”
Section: Role Of Ceramides In Shaping the Structure Of Membranesmentioning
confidence: 98%